Sexual Dimorphism in Estimated Stature from Long Bones in Gilimanuk, Semawang, Plawangan, and Recent Sample in Indonesia - Hastuti, Janatin; Prayudi, Ashwin; Rahmawati , Neni Trilusiana; Fauzi, Noorman Hendry; Suriyanto, Rusyad Adi (Anthropological Review, 2025)
The study of sexual dimorphism among ancient skeletons can provide information on community health in the past. Meanwhile, the younger geological age of skeletal remains from Gilimanuk, Semawang, and Plawangan have received little attention. This study aimed to evaluate the sexual dimorphism in estimated stature of Gilimanuk, Semawang, Plawangan, in addition to a recent sample, of long bones. Observations were conducted on 44 (16 males, 28 females) skeletal remains of Gilimanuk, nine of Semawang (five males, four females) and 11 of Plawangan, (four males, seven females), and nine of recent (four males, five females) human skeletons stored at Universitas Gadjah Mada, Yogyakarta, Indonesia. Stature was estimated from the length of long bones. The highest average stature in the ancient sample was for Gilimanuk females (168.74 ± 9.18 cm) and males (174.10 ± 9.42 cm) in the age 16–<20 years. However, the averages of estimated stature in all ages were similar in both sexes. The average estimated stature of Semawang and Plawangan remains was slightly lower than those of Gilimanuk remains, i.e., 162.60 ± 3.97 and 159.08 ± 1.59 cm, respectively. In comparison, the recent human skeletons indicated that the average estimated stature was 168.32 ± 4.70 for males and 160.45 ± 6.89 cm for females. Our findings indicate that long bone measurements are comparable among remains from each sample. However, sexual dimorphism in estimated stature was clearly greater in recent human remains in comparison to Gilimanuk, Semawang, and Plawangan skeletal remains. Our findings suggest temporal changes in stature in this part of Indonesia.